1520 Decoding Neurophobia – Insights from an Undergraduate Neuroanatomy Course. (12th October 2021) - Bhate, R; Colman, J; Fowler, T; Hayley, J; Kallam, N; Mak, T L A; Matthews, F; Norton, E; Richardson, D
Abstract: Introduction: Neurophobia is a common multifaceted issue amongst students studying medical sciences at an undergraduate level associated with difficulty in understanding neuroscience topics and ongoing negative perceptions of clinical neurosciences. We sought to examine whether neurophobia was present even amongst students who participated in an extracurricular neuroanatomy teaching course. Method: Prior to the beginning of a twelve-week online neuroanatomy course, delegates were asked to complete a short questionnaire examining perceptions of neurophobia and specialities of interest. This was repeated after the course. This course was open to all undergraduate students in the UK and covered material beyond the remits of the undergraduate curriculum. Results: From the 166 signups, 98 students completed the pre-course questionnaire. As expected, the majority of students (n = 83) taking part did not identify as neurophobic, describing the subject area as 'interesting', 'enjoyable' and 'challenging'. Students who identified as neurophobic described neuroanatomy as 'complex' or 'overwhelming'. Some students (n = 12) continued to describe themselves as neurophobic at the end of the course, despite this 7 of those students continue to consider a future career in a neuro-related speciality. Conclusions: The fact that students with Neurophobia attended this extra-curricular course speaks volumes of how perception and self-motivation of a student are important for learning a subject. All students who participated in this course recognised the complexity and interesting nature of neuroanatomy. This experience highlights the challenge of medical educators to provide teaching experiences that are stimulating and enjoyable, but not overwhelming.